A Framework for 5G and Beyond, Non-Terrestrial Networks, and V2X - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Würzburg Workshop on 6G Networks (WueWoWAS’24), 2024)
The integration of 5G and beyond Non-Terrestrial Networks with vehicular applications addresses critical challenges, such as ensuring ultra-reliable low-latency communication (URLLC) and supporting enhanced mobile broadband (eMBB) services. This convergence is expected to improve road safety, traffic efficiency, and enable advanced autonomous driving capabilities. In this paper we aim to provide a first overview of the evaluation results in the context of vehicle to everything (V2X

TCP CUBIC with HyStart: Congestion Control for Satellite Communication in OMNeT++ INET - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (2024 IEEE 29th Asia Pacific Conference on Communications (APCC), 2024)
In the context of satellite communication, unique challenges arise, such as long delay links that can impact the network performance also at the Transport Layer. With regard to the Transmission Control Protocol (TCP), congestion control plays a crucial role in managing network traffic and ensuring efficient data transmission over the Internet. This paper wants to give an overview of how TCP congestion control mechanisms adapt to mitigate the effects of long link delays, highlighting the importance of optimizing protocols for these specific environments. Within this context, where signals travel extended distances, traditional TCP algorithms designed for terrestrial networks with relatively low latency, may struggle to maintain optimal performance. As a result, specialized congestion control algorithms, like TCP CUBIC, can be employed to address these challenges. Through the integration of TCP CUBIC with HyStart within a simulation framework based on OMNeT++ and INET, this study sheds light on the importance of tailoring congestion control strategies to suit specific network environments including satellite communicatio

Towards a 5G Satellite Communication Framework for V2X - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (Würzburg Workshop on Modeling, Analysis and Simulation of Next-Generation Communication Networks 2023 (WueWoWAS’23), 2023)
In recent years, satellite communication has been expanding its field of application in the world of computer networks. This paper aims to provide an overview of how a typical scenario involving 5G Non-Terrestrial Networks (NTNs) for vehicle to everything (V2X) applications is characterized. In particular, a first implementation of a system that integrates them together will be described. Such a framework will later be used to evaluate the performance of applications such as Vehicle Monitoring (VM), Remote Driving (RD), Voice Over IP (VoIP), and others. Different configuration scenarios such as Low Earth Orbit and Geostationary Orbit will be considered.<br

Towards a comparative study of application performance in an automotive environment with 5G non-terrestrial networks - Martino, Luigi; Deutschmann, Jörg; Hielscher, Kai-Steffen; German, Reinhard (IET, 2024)
Non-Terrestrial Networks (NTNs), and in particular satellite networks, are emerging as a promising solution to extend the coverage and capacity of wireless networks beyond the limitations of terrestrial infrastructure. One such technology that has been heavily researched in recent years is 5G, which promises to improve the way we communicate by providing high data rates, machine-to-machine communications and ultra-reliable low-latency communications. In particular, the automotive industry is expected to greatly benefit from 5G, as it can enable a range of advanced applications such as autonomous driving, vehicle-to-vehicle (V2V) and vehicle- to-infrastructure (V2I) communications. However, the deployment of 5G in vehicular environments is still facing significant challenges, such as ensuring reliable and secure communication, providing efficient mobility management, and optimizing the use of radio resources. In this context, this paper provides an overview of automotive applications such as Voice over IP (VoIP), Vehicle Monitoring (based on UDP) and a file bulk transfer (based on TCP) over a Geostationary and Low Earth Orbit link, highlighting the key issues and potential solutions to enable the seamless integration of vehicular communications into these emerging network